-4(-k-2)=2k-34

Simple and best practice solution for -4(-k-2)=2k-34 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(-k-2)=2k-34 equation:


Simplifying
-4(-1k + -2) = 2k + -34

Reorder the terms:
-4(-2 + -1k) = 2k + -34
(-2 * -4 + -1k * -4) = 2k + -34
(8 + 4k) = 2k + -34

Reorder the terms:
8 + 4k = -34 + 2k

Solving
8 + 4k = -34 + 2k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-2k' to each side of the equation.
8 + 4k + -2k = -34 + 2k + -2k

Combine like terms: 4k + -2k = 2k
8 + 2k = -34 + 2k + -2k

Combine like terms: 2k + -2k = 0
8 + 2k = -34 + 0
8 + 2k = -34

Add '-8' to each side of the equation.
8 + -8 + 2k = -34 + -8

Combine like terms: 8 + -8 = 0
0 + 2k = -34 + -8
2k = -34 + -8

Combine like terms: -34 + -8 = -42
2k = -42

Divide each side by '2'.
k = -21

Simplifying
k = -21

See similar equations:

| 9+3-7-8+18-3= | | 6(-1-6x)=-6-6x | | X+2x^2=36 | | 1/6+x/9=x/12 | | 38+8n=-6(1+6n) | | 2x-2y+3x= | | 0.8x=128 | | y^2+361/4=-19y | | 12d^2-d-6=0 | | 3bx*x-2ax+3b=0 | | 3bx*x-2ax+3y=0 | | 3bx*x-2ax+by=0 | | x^6-1/27=0 | | 4n+7n= | | -8(x-8)+x=2(7-x) | | x(x-6)=x^2+4x+3 | | x(x-6)=x^2+6x+11 | | 5x^2-11x-4=0 | | 60(5/12) | | 60(4/5) | | 60(x/4) | | 12(2k+11)=12(2k-12) | | -7-(-1)/-8-(-3)=-6/(-5) | | 2(3y-5)=44 | | 4r^2+9=125 | | 9x-2(x-6)=7(x+1)+2 | | 2(x+9)=19 | | 4x+4=60 | | 11r+5=-2r^2 | | (2x+12)/(3x+12)=8/11 | | y=12.5x+200 | | 1.7(7-x)=1.5(5-x) |

Equations solver categories